Apolipoprotein E polymorphism and renal function in German Type 1 and Type 2 diabetic patients - Werle, Egon; Fiehn, Walter; Hasslacher, Christoph (Diabetes care, 1998)
To examine the association of renal function in diabetic patients with apolipoprotein (apo) E polymorphism.Apo E genotypes, lipid and lipoprotein serum levels, creatinine clearance (CCr), and excretion of marker proteins were determined in German type 1 (IDDM; n = 162) and type 2 (NIDDM; n = 124) diabetic patients. Albumin and immunoglobulin (Ig) G are considered to reflect charge-size permselectivity of the glomerular capillary basement membrane, and increased alpha 1-microglobulin (MG) excretion indicates compromised reabsorptive capacity of the renal tubules.Patients with NIDDM had higher lipid levels and lower CCrs than patients with IDDM. In patients with IDDM, age- and sex-adjusted analysis of variance showed an association between apo E genotypes and CCr, and the Jonckheere-Terpstra test demonstrated a decreasing glomerular filtration rate in the following order of genotypes: ε4ε4/ε4ε3 > ε3ε3 > ε2ε2/ε2ε3. Multiple linear regression analyses revealed that in patients with IDDM, the ε2 allele was a negative predictor of CCr and a positive predictor of urinary excretion of albumin, IgG and α 1-MG independent from HDL and LDL cholesterol, TG concentration, age, and sex.Apo E polymorphism influences serum lipoprotein levels in patients with IDDM and NIDDM. Apo E polymorphism may be a renal risk factor of clinical relevance in normolipidemic patients with IDDM.
Gesehen am 06.02.2025